Pengembangan Modul Pelatihan Literasi Digital dalam Peningkatan Kompetensi Pedagogik dengan Alat Bantu Arttificial Intelegence (AI) di SD Distrik Waibu - Yosina Dike; Bambang Ismanto (Attractive : Innovative Education Journal, 2025)
This study aims to develop a digital literacy training module assisted by Artificial Intelligence (AI) to improve the pedagogical competence of elementary school teachers in Waibu District. The type of research is Research and Development (R&D) using the ADDIE model (Analysis, Design, Develop, Implement, Evaluate). The research location is SD Inpres Doyo Lama and SD Kristen Alam Indah with field trial subjects of 21 teachers. Data collection through validation sheets, practicality sheets, questionnaires, and tests. Data analysis techniques include descriptive percentage analysis, Paired Sample T-Test, and N-Gain Score. The results showed that the material and media expert validators rated the module valid with an average score of 3.46 and 3.31, respectively. Practitioners rated the module very practical with a percentage of 87.08%. The effectiveness test proved the module provided a significant increase with a significance value of 0.000 and an N-Gain score of 0.61 in the moderate category. The researcher concluded that this module is feasible and effective in improving teachers' digital literacy skills and pedagogical competence. Researchers suggest teachers form learning communities to share good practices in using AI.